Faster modified protocol for first order reversal curve measurements - de Biasi, Emilio (2017)
In this work we present a faster modified protocol for first order reversal curve (FORC) measurements. The main idea of this procedure is to use the information of the ascending and descending branches constructed through successive sweeps of magnetic field. The new method reduces the number of field sweeps to almost one half as compared to the traditional method. The length of each branch is reduced faster than in the usual FORC protocol. The new method implies not only a new measurement protocol but also a new recipe for the previous treatment of the data. After of these pre-processing, the FORC diagram can be obtained by the conventional methods. In the present work we show that the new FORC procedure leads to results identical to the conventional method if the system under study follows the Stoner-Wohlfarth model with interactions that do not depend of the magnetic state (up or down) of the entities, as in the Preisach model. More specifically, if the coercive and interactions fields are not correlated, and the hysteresis loops have a square shape. Some numerical examples show the comparison between the usual FORC procedure and the propose one. We also discuss that it is possible to find some differences in the case of real systems, due to the magnetic interactions. There is no reason to prefer one FORC method over the other from the point of view of the information to be obtained. On the contrary, the use of both methods could open doors for a more accurate and deep analysis.